Student Grade Prediction Using R Language - Mahalakshmi Phaldesai, Prachi Kumar, Kiran Ingale, Tanushri Bhuruk, Ritesh Pokarne, Nikita Punde (Mathematical Statistician and Engineering Applications, 2022)
In today’s world all major companies store their records together in some kind of database or an excel sheet and it is very important to keep this data cleaned and up to date to avoid any confusion and be safe, secure .This is where the concept of data science comes into picture which not only used the data we stored in excel sheets but is used to find patterns within our dataset. Then we use these patterns to make valuable insights and some data derived decisions like predicting the values for the dataset or classifying the data into some parts and then comparing with the known values to check the accuracy of the built model .There are various processes like data extraction, preprocessing, cleaning through which our dataset has to go for getting a final result which is necessary for a better prediction and then our main model code is being implemented in the way we want to work with the data and get the output. This paper deals with the student grade prediction system predicting the grade of a student.